2018
DOI: 10.1186/s13046-018-0974-1
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane protein GRINA modulates aerobic glycolysis and promotes tumor progression in gastric cancer

Abstract: BackgroundRecent observations indicate a decreased cancer risk in patients with Alzheimer’s disease (AD). AD is a severe neurodegenerative disorder characterized by progressive cognitive decline. The 8q24 region has been shown to be involved in AD aetiology. We aimed to identify and explore the potential oncogenes or antioncogenes on chromosome 8q24.MethodsWe compared expression of genes on Chromosome 8q24 in 32 pairs of samples from The Cancer Genome Atlas (TCGA) database. We conducted bioinformatics analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…Members of the TMBIM family such as TMBIM1, TMBIM2, TMBIM4, and TMBIM5 are found to be expressed highly in various cancers and also play an important role in cell adhesion and migration [81,82,83,84]. Additionally, TMBIM3 found to be involved in the gastric cancer progression by modulating the glycolytic metabolism [85]. These observations corroborate the high expression of TMBIM6 and its importance in cancer.…”
Section: Discussionmentioning
confidence: 60%
“…Members of the TMBIM family such as TMBIM1, TMBIM2, TMBIM4, and TMBIM5 are found to be expressed highly in various cancers and also play an important role in cell adhesion and migration [81,82,83,84]. Additionally, TMBIM3 found to be involved in the gastric cancer progression by modulating the glycolytic metabolism [85]. These observations corroborate the high expression of TMBIM6 and its importance in cancer.…”
Section: Discussionmentioning
confidence: 60%
“…The expression of GRINA is upregulated in breast cancer, colorectal cancer and gastric cancer [13]. A recent article [87] confirmed that GRINA is upregulated in gastric cancer and that its regulation is mediated by c-Myc. The authors found that upon knockdown of GRINA, antiapoptotic Bcl-2 and Bcl-XL were downregulated, while proapoptotic Bax and Bak were upregulated.…”
Section: Transcriptional Regulation Of Grinamentioning
confidence: 99%
“…DEGs are mainly concentrated in angiogenesis, oncostatin-M-mediated signaling pathway, Cytokinecytokine receptor interaction and Glycolysis / Gluconeogenesis. Studies have reported that angiogenesis and glycolysis have a substantial impact on the occurrence and development of gastric cancer [29,30]. In addition, recent studies have found that cytokine-cytokine receptor interactions play an important role in the development of gastric cancer [31].…”
Section: Discussionmentioning
confidence: 99%